2021
DOI: 10.1016/j.ssmph.2021.100838
|View full text |Cite
|
Sign up to set email alerts
|

Masculinity and men's health service use across four social generations: Findings from Australia's Ten to Men study

Abstract: There is a perception that traditional masculine ideals, usually thought deleterious for men's health outcomes, are no longer as relevant for younger social generations such as Millennials as they are for older social generations such as Baby Boomers. Yet, in Australia, there remains a disparity between younger men's and women's health outcomes and use of health services. Conformity to traditional masculinity is often cited as a barrier to men's positive health behaviours but conceptualisation of the construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Conformity to masculine norms is linked to many adverse mental and physical health outcomes ( Mahalik et al, 2003 ; McGraw et al, 2021 ; Milner et al, 2019 ; Salgado et al, 2019 ). For example, adherence to Violence, Dominance as well as Risk-taking has been linked to psychological distress through somatization among men ( Mahalik et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conformity to masculine norms is linked to many adverse mental and physical health outcomes ( Mahalik et al, 2003 ; McGraw et al, 2021 ; Milner et al, 2019 ; Salgado et al, 2019 ). For example, adherence to Violence, Dominance as well as Risk-taking has been linked to psychological distress through somatization among men ( Mahalik et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, adherence to Violence, Dominance as well as Risk-taking has been linked to psychological distress through somatization among men ( Mahalik et al, 2003 ). More recently, McGraw and colleagues’ (2021) study revealed that Emotional control, Self-reliance, and Violence predicts different generations’ likelihood of decreased regular health service use. Language also plays a determinant role in health ( Bowen, 2001 ; de Moissac & Bowen, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also findings that increased endorsement of specific TMI domains are associated with increased willingness to use health care services. Namely, endorsement of the belief that men need to attain high social status in a group or that men always need to be the best has been shown to be linked to increased use of health care services (McGraw et al, 2021;Sileo & Kershaw, 2020). It seems important to note, that recent reports found no or even beneficiary relations between individual masculine norms and negative mental health outcomes, such as depression symptoms (Lin et al, 2021;Van Doorn et al, 2021).…”
Section: Traditional Masculinity Ideologiesmentioning
confidence: 99%